2019
DOI: 10.1021/acsami.9b14793
|View full text |Cite
|
Sign up to set email alerts
|

MIL-100(Fe)/Ti3C2 MXene as a Schottky Catalyst with Enhanced Photocatalytic Oxidation for Nitrogen Fixation Activities

Abstract: A new microporous MIL-100­(Fe)/Ti3C2 MXene composite was constructed as a non-noble metal-based Schottky junction photocatalyst with improved nitrogen fixation ability. Ti3C2 MXene nanosheets exhibited excellent metal conductivity and were employed as two-dimensional support to optimize the composite’s energy band structure. MIL-100­(Fe) with a large specific surface area was used as an adsorbent and a photocatalytic oxidation center. The MIL-100­(Fe)/Ti3C2 MXene composite not only exhibited higher thermal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(86 citation statements)
references
References 117 publications
1
78
0
Order By: Relevance
“…Until 2013, Yuan et al demonstrated the oxidation of N 2 in air to HNO 3 on TiO 2 under sunlight, and NO was found to be an intermediate in this process, in which two possible mechanisms of photocatalytic N 2 oxidation to NO were proposed based on the theoretical calculation. [ 34 ] According to this statement and combination with the other studies in this field, [ 33,68 ] the following two mechanisms of photocatalytic NOR are drawn in Figure .…”
Section: Fundamentals Of Photocatalytic Nitrogen‐fixation Reactionsmentioning
confidence: 92%
See 2 more Smart Citations
“…Until 2013, Yuan et al demonstrated the oxidation of N 2 in air to HNO 3 on TiO 2 under sunlight, and NO was found to be an intermediate in this process, in which two possible mechanisms of photocatalytic N 2 oxidation to NO were proposed based on the theoretical calculation. [ 34 ] According to this statement and combination with the other studies in this field, [ 33,68 ] the following two mechanisms of photocatalytic NOR are drawn in Figure .…”
Section: Fundamentals Of Photocatalytic Nitrogen‐fixation Reactionsmentioning
confidence: 92%
“…In principle, NOR will occurs when the N 2 molecule eventually loses the electrons on catalyst surface, and the products are generally considered to be NO and NO 3 − (the product of further oxidation of NO). [ 33–35,68 ] At this occasion, the photoexcited electrons in the CB of semiconductor are usually transferred to O 2 molecule. The involved equations are as followsnormalN2+normalO22NO4NO+3normalO2+2normalH2O4HNO3…”
Section: Fundamentals Of Photocatalytic Nitrogen‐fixation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interfaces between two adjacent components play a vital role in charge carriers transfer, because the structure of interface impacts electron–hole pair migration from light‐harvesting component to surface active sites. [ 342–345 ] As a typical metal–semiconductor junction and one of the most desirable semiconductor–semiconductor junctions, Schottky junction and Z‐scheme junction will be discussed here.…”
Section: Interfacial Structure In Heterojunctionmentioning
confidence: 99%
“…The absorption peaks at 1629 and 1375 cm −1 are attributed to the C O and C O stretching vibrations, respectively. The bands at 760 and 713 cm −1 are assigned to bending vibrations of C H on the benzene ring, and the band at 481 cm −1belongs to Fe O stretching vibrations 40. In curve b, the wide peak centered at 3425 cm −1 belongs to the stretching vibrations of the O H. The two distinct peaks at 1570 and 1387 cm −1 correspond to asymmetric and symmetric vibrations of carboxyl groups,41 respectively.…”
mentioning
confidence: 99%